Buckling failure in air-plasma sprayed thermal barrier coatings induced by molten silicate attack. (1st March 2016) - Shan, Xiao; Zou, Zhonghua; Gu, Lijian; Yang, Lixia; Guo, Fangwei; Zhao, Xiaofeng; Xiao, Ping
Abstract: The buckling phenomenon in air-plasma sprayed yttria-stabilized zirconia (YSZ) thermal barrier coatings (TBCs) induced by calcium–magnesium-alumino-silicate (CMAS) attack was investigated. The liquid CMAS infiltration due to capillary force weakened the interface and introduced a significant volume expansion (32%) in the top coat, leading to a large scale buckling of the TBC at high temperature. The dissolution and tetragonal-mononiclic phase transformation of YSZ induced by CMAS only has a negligible contribution. Graphical abstract: